PERAN PEMERINTAH DESA TERHADAP PENINGKATAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN (STUDI KASUS DESA MALIAYA KECAMATAN MALUNDA KABUPATEN MAJENE) - Munawir Arifin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2017)
The purpose of this study was to determine community participation in the implementation of development in Maliaya Village Malunda District, to find out the role of the village government in encouraging community participation in the implementation of development in Maliaya Village Malunda Subdistrict, and to find out the inhibiting factors and drivers that influence community participation in the implementation of development in Maliaya Village. This research was conducted in Maliaya Village, Malunda Subdistrict, Majene Regency, from January to February 2017. The method used in this study was to use a descriptive research form with qualitative data analysis. The results of the study show that the community is a factor supporting the development in the village is not good enough when viewed from the low participation of the community of Maliaya village.